2016
DOI: 10.4269/ajtmh.16-0059
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B Virus Infection in Kenya, 2007

Abstract: Abstract. Current estimates put the prevalence of hepatitis B virus (HBV) infection in Kenya at 5-8%. We determined the HBV infection prevalence in the human immunodeficiency virus (HIV)-negative Kenyan adult and adolescent population based on samples collected from a national survey. We analyzed data from HIV-negative participants in the 2007 Kenya AIDS Indicator Survey to estimate the HBV infection prevalence. We defined past or present HBV infection as presence of total hepatitis B core antibody (HBcAb), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 11 publications
2
32
5
Order By: Relevance
“…). Seroprevalence of Hepatitis B surface antigen (HBsAg) in adults in the mid Northern region is the highest in Uganda, at 4.6%, more than double that in Kampala and Kenya …”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…). Seroprevalence of Hepatitis B surface antigen (HBsAg) in adults in the mid Northern region is the highest in Uganda, at 4.6%, more than double that in Kampala and Kenya …”
Section: Discussionmentioning
confidence: 73%
“…Seroprevalence of Hepatitis B surface antigen (HBsAg) in adults in the mid Northern region is the highest in Uganda, at 4.6%, more than double that in Kampala 14 and Kenya. 16 On the other hand, the incidence of oesophageal cancer, although relatively high by global standards, is rather lower than the elevated rates seen in many registries of East Africa, 17 although showing the marked excess of male cases, typical of this high risk region. 18 In this predominantly rural population, it was not surprising to find that cancers associated with more urbanised/westernised lifestyles-such as large bowel cancer and breast cancer -were relatively uncommon.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, when possible, we suggest that prevalence should be evaluated at the whole country level in order to highlight potential differences between regions and/or communities. 21,51,53,54 This finding warrants further investigation to reveal whether specific genetic or cultural factors influence HDV transmission. Finally, HBV and HDV genotyping revealed a high genetic diversity of the strains circulating in Gabon, including many restricted to this region of the globe.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, we reported a North‐South split in the distribution of HDV seroprevalence, with the highest rates (>66.0%) correlating with the presence of specific ethnic groups in the northeastern provinces. Thus, when possible, we suggest that prevalence should be evaluated at the whole country level in order to highlight potential differences between regions and/or communities . This finding warrants further investigation to reveal whether specific genetic or cultural factors influence HDV transmission.…”
Section: Discussionmentioning
confidence: 90%
“…43,44 A study from Kenya reported an HBsAg prevalence rate of 2.1% in adult residents of a rural area. 45 Reports of HCV prevalence in Rwanda vary markedly. Our finding of an HCV prevalence rate of 1.8% is substantially lower than other surveys conducted in Rwanda, which report HCV prevalence rates of 3.1% in the general population, 4.7% in HIV-infected adults and 9.6% in patients attending Rwanda Military Hospital.…”
Section: Discussionmentioning
confidence: 99%